2017
DOI: 10.1371/journal.pone.0170395
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice of analysis of anti-drug antibodies against interferon beta and natalizumab in multiple sclerosis patients in Europe: A descriptive study of test results

Abstract: Antibodies against biopharmaceuticals (anti-drug antibodies, ADA) have been a well-integrated part of the clinical care of multiple sclerosis (MS) in several European countries. ADA data generated in Europe during the more than 10 years of ADA monitoring in MS patients treated with interferon beta (IFNβ) and natalizumab have been pooled and characterized through collaboration within a European consortium. The aim of this study was to report on the clinical practice of ADA testing in Europe, considering the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
1
23
0
3
Order By: Relevance
“…Tocilizumab and rituximab also resulted in a higher ADA incidence in the ABIRISK prospective study than in previous reports, likely because of the sensitivity and drug tolerance of the MSD assay, which has not been used before for detecting ADAs against these BPs in RA [ 54 57 ]. Concerning the other biologicals analyzed in this study, the broad immunogenicity level was comparable to what has been previously reported [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 89%
“…Tocilizumab and rituximab also resulted in a higher ADA incidence in the ABIRISK prospective study than in previous reports, likely because of the sensitivity and drug tolerance of the MSD assay, which has not been used before for detecting ADAs against these BPs in RA [ 54 57 ]. Concerning the other biologicals analyzed in this study, the broad immunogenicity level was comparable to what has been previously reported [ 58 , 59 ].…”
Section: Discussionsupporting
confidence: 89%
“…The therapeutic use of monoclonal antibodies and other biopharmaceutical products can result in an immune response to the drug that, in some cases, affects its efficacy due to the production of neutralizing ADAs 5 . Several clinical studies have measured ADA levels in sera of selected cohorts of patients and concluded that not all antibody responses lead to drug neutralization [6][7][8][9][10][11] . However, an explanation for these heterogeneous responses and an integrated characterization of the B and T cell responses to the drug are still missing.…”
mentioning
confidence: 99%
“…Development of ADAs can affect safety or efficacy 11,[28][29][30] may not be recognized until the commencement of large expensive phase 3 clinical studies 5 or even after approval. [31][32][33][34][35] This latestage failure of drugs adds considerable economic risk for the biotechnology industry. More important, the potential consequences of immunogenicity for a subject in a clinical study range from loss in quality of life 36 to a life-threatening situation.…”
Section: Discussionmentioning
confidence: 99%